INTEGRASI TEKNOLOGI DIGITAL DALAM PEMBELAJARAN EKONOMI : STUDI KASUS PADA MAHASISWA JURUSAN PENDIDIKAN EKONOMI - Imam Prawiranegara Gani; Unan Yusmaniar Oktiawati; Hayati; Abraham Manuhutu; Riri Wulandari; Ade Taufan (EDU RESEARCH, 2024)
Technological infrastructure issues include hardware shortages, lack of skills and competencies in integrating digital technology into learning processes, lack of motivation and motivation for students to use digital technology in economic learning, insufficient integration of digital content, and unclear guidelines and policies from school authorities regarding digital integration in learning processes. This study aims to analyse the integration of digital technology in teaching economics to students of Gorontalo State University. The research method used is a case study with a qualitative approach. Data were collected through interviews, observations, and documentation. The results showed that the integration of digital technology in teaching economics at Gorontalo State University has been carried out in several forms, such as the use of e-learning platforms, the utilisation of digital economic applications, and the development of digital content. The obstacles faced include infrastructure readiness, lecturer competence, and student interest in learning. Strategies to overcome these obstacles are improving digital facilities, training lecturers, and strengthening student learning motivation. This research implies that the integration of digital technology in teaching economics can improve the quality of learning and student competence, and support digital transformation in educational institutions.